Evaluasi Penggunaan Insulin pada Pasien Diabetes Melitus Tipe 2 Rawat Jalan di Rumah Sakit X di Jakarta Periode 2016-2017 - Anggriani, Yusi; Rianti, Alfina; Pratiwi, Annisa Nadya; Puspitasari, Wulan (Fakultas Farmasi Universitas Andalas, 2020)
Type 2 Diabetes Mellitus (DMT2) is a metabolic disease with the characteristics of hyperglycemia that occurs due to abnormal insulin secretion. One of the treatments of DM is insulin therapy. Based on its provenance, insulin consists of human insulin and analogue insulin. This study was conducted to identify profiles of insulin used in DMT2 patients at RSUP X hospital in Jakarta. This was an observational study conducted retrospectively on data from 2016 to 2017. The total sample numbers of DMT2 outpatients using insulin were 218 in 2016, and 225 in 2017. Data on insulin therapy regimens were obtained from medical records and drug use reports. The results obtained from this study indicated that the type of insulin that was widely used by DMT2 outpatients was analogue insulin with a percentage of 99%. The human insulin was rarely used in outpatients. The highest use of analogue insulin was analog premixed insulin (35%).